Two-step recommendations: contrast analysis and matrix factorization techniques - Aleksandrova, M.; Brun, A.; Boyer, A.; Chertov, O. (Математичні машини і системи, 2014)
In this paper we present a two-step recommendation model based on Contrast Analysis and Matrix Factorization techniques which mutually complement each other. We also provide a brief overview of different Matrix Factorization approaches.